IDEOLOGICAL ORGANIZATIONS: A COMPARATIVE STUDY BETWEEN FRANCE AND BRAZIL - Munhoz Machado Prigol Zdrojewski, Natalia (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
The research aims to analyze how Ideological Organizations are juridically treated in France and in Brazil though a comparative study. As it will be show, Ideological Organizations are those entities created to defend an ideology, such as churches, political parties, labor unions, religion organizations, etc. In those organizations, different from what normally occurs in labor relationship, the employer can compel his employees to have conducts inside and outside the workplace that are similar with the ideology that the Organization defends. It is an exemption from what normally occurs in French and Brazilian labor relations. In French this legal institute is well applied by Courts, promoting stability, despite the fact that is not expressly regulated by the law. In Brazil, in the other hand, there is no legal certainty because the institute is not recognized by the labor law and, as a result of that, Courts significantly diverge while judging labor claims involving Ideological Organizations. The research is performed trough a deductive method.